Seas upon sea - Silva, Douglas Gomes (Revista do Colóquio, 2026)
This article analyzes the relationships between art, city, and landscape based on the 8th Biennial Sea Salon: Waves, Bridges, and Navigable Interventions (2008/2009), a contemporary public art exhibition held in Vitória, Espírito Santo (Brazil). Based on documentary research and critical analysis, the study examines the works We See the City as the City Sees Us, by Heraldo Ferreira; The Silence of the Hammer, by Fabrício Carvalho; Path of the Waters, by Piatan Lube; and The Return of Araribóia, by the Maruípe Collective. The investigation seeks to understand how these interventions are integrated into the urban space, speaking of the sea, for the sea, and about the sea, and how they act upon the landscape, interfering, in distinct ways, with the memorial, institutional, and symbolic layers of the city.